The Effect of Firm Size, Liquidity Ratio, and Leverage on The Profitability of The Financial Sector In Indonesia in The 2024 Period - Sheila Rizqya Listy; Imronudin (PT Keberlanjutan Strategis Indonesia, 2026)
The financial sector is one of the main foundations supporting the stability and growth of the Indonesian economy. This sector's role is increasingly crucial as the complexity of business activities and the need for flexible funding increase. Profitability serves as a fundamental benchmark for evaluating the stability and operational success of firms within the financial industry. This research examines how variations in Firm Size, Liquidity Ratio, and Leverage contribute to shaping the profitability performance of financial institutions in Indonesia throughout 2024. Profitability is assessed using two principal indicators—Return on Assets (ROA) and Net Profit Margin (NPM)—which illustrate the degree to which firms can efficiently utilize their assets and convert revenue streams into net income. Employing a quantitative design, the study relies on secondary data derived from the 2024 annual financial statements of 97 financial-sector entities listed on the Indonesia Stock Exchange (IDX). The analysis utilizes a multiple linear regression framework, supported by a full range of classical assumption tests, to evaluate the interactions among the variables. The results indicate that Firm Size has a statistically significant effect on ROA, while its influence on NPM is not found to be significant. The Liquidity Ratio does not affect either profitability indicator. Leverage does not affect ROA, but significantly influences NPM. Simultaneously, all three independent variables significantly influence profitability in both the ROA and NPM models. These outcomes carry notable implications for both financial decision-makers and market participants: company size and debt-based financing structure can impact profitability differently depending on the indicators used.